2011
DOI: 10.1038/ejcn.2011.81
|View full text |Cite
|
Sign up to set email alerts
|

Habitual dietary intake, eating pattern and physical activity of women with polycystic ovary syndrome

Abstract: Background/Objective: Diet and lifestyle modifications may be of benefit in the management of polycystic ovary syndrome (PCOS), but there is a paucity of data on these behaviours in women with PCOS. This study aims to address this through a comprehensive investigation of the habitual diet and activity patterns of UK women with PCOS and their alignment with dietary recommendations for health. Subjects/Methods: A 7-day-estimated food and activity diary and questionnaire was completed by 210 women with PCOS for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 42 publications
6
38
3
Order By: Relevance
“…However, data accuracy may be limited as a result of the ability of the responders to remember their intake. Moreover, women with PCOS reported higher carbohydrate (229 versus 61 g), protein (78 versus 66.3 g), fat (85 versus 61.1 g), saturated fat (26 versus 22.5 g) intake compared to the reference population . A high energy diet has been reported in Iranian and Brazilian women with PCOS.…”
Section: Discussionmentioning
confidence: 89%
“…However, data accuracy may be limited as a result of the ability of the responders to remember their intake. Moreover, women with PCOS reported higher carbohydrate (229 versus 61 g), protein (78 versus 66.3 g), fat (85 versus 61.1 g), saturated fat (26 versus 22.5 g) intake compared to the reference population . A high energy diet has been reported in Iranian and Brazilian women with PCOS.…”
Section: Discussionmentioning
confidence: 89%
“…Exercise-only methods seem to be insufficient and a combination with dietary modifications, caloric restrictions and behavioural interventions is required. Attention should be paid to fat quality and quantity and to carbohydrate modification, although further research is needed to assess the role of dietary glycaemic index in PCOS [78]. According to a recent meta-analysis, lifestyle intervention improved biochemical and endocrinological parameters including body composition, insulin resistance and hyperandrogenism, although it had no effect on glucose tolerance and lipid profile [79].…”
Section: Lifestyle Changes In Pcosmentioning
confidence: 97%
“…It has been estimated that approximately half of the overweight women with PCOS are not achieving sufficient physical activity to promote weight loss [78]. There are various methods that can be used to treat obesity in PCOS patients.…”
Section: Impact Of Obesity Treatment On Pcosmentioning
confidence: 99%
“…However, no previous study have investigated whether meal patterns of women with PCOS differ from those of healthy women. The one study that reported habitual meal patterns in women with PCOS did not include healthy women [14], thus the importance of the frequency of food intake in women with PCOS has yet not been determined. Eating attitudes might also be affected in women with PCOS, and it has been suggested that high androgen levels and polycystic ovaries might advance bulimic behavior by influencing food cravings and impulse control [15].…”
Section: Introductionmentioning
confidence: 98%